Tuan Guru in Lombok: Their Role and Influence in Education and Local Politics During the Reform Era - Anwar, Muh. Samsul; Sukamdani, M. (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This study explores the evolving role of Tuan Guru (Islamic leaders) in Lombok during the post-New Order era, emphasizing their influence in both education and local politics. During the New Order period, Tuan Guru's roles were largely symbolic, with limited impact in the legislative or executive realms dominated by the Menak group. However, political reforms led to a significant shift, enabling Tuan Guru to gain a more prominent role in Sasak society's political and educational spheres, alongside the resurgence of Islamic political activism. The candidacy and subsequent victory of TGB Muhammad Zainul Majdi in the 2008 West Nusa Tenggara regional elections exemplify this shift, showcasing the transition of Tuan Guru from purely religious leadership to a more integrated role in political and educational domains. His success marked a departure from the traditional Menak dominance, highlighting the appeal of Tuan Guru as credible and clean alternatives in an era of political corruption. This qualitative study employs descriptive analysis and extensive library research, utilizing primary and secondary sources such as books, journals, archival documents, and relevant writings. The research underscores Tuan Guru's growing influence in shaping both the educational landscape and local politics in Lombok within the broader context of Islamic movements in Indonesia.